2021
DOI: 10.18549/pharmpract.2021.1.2317
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards COVID-19 vaccination, vaccine hesitancy and intention to take the vaccine

Abstract: Background: The pandemic is at a paradoxical stage, with vaccine roll out initiated but a significantly elevated level of infection and death. Hope for recovery lies in high equitable vaccine uptake. Objective: The study aimed to: i) explore attitudes and factors influencing attitudes, towards the COVID-19 vaccine amongst people living in Malta, ii) identify the reasons as to why individuals are unsure or unwilling to take the vaccine. Methods: Two consecutive, short, anonymous online surveys using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
168
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(202 citation statements)
references
References 35 publications
26
168
5
3
Order By: Relevance
“…Our findings show that Parler users discuss several reasons for vaccine refusal and skepticism regarding the efficacy of the vaccine, refusal among healthcare workers to get vaccinated, and potential side effects of the vaccine. These findings are similar to previous research which reveal several reasons individuals choose to refuse vaccines [53]. The results from the first theme (reasons to refuse COVID-19 vaccines) show that users raise important and legitimate concerns…”
Section: Discussionsupporting
confidence: 90%
“…Our findings show that Parler users discuss several reasons for vaccine refusal and skepticism regarding the efficacy of the vaccine, refusal among healthcare workers to get vaccinated, and potential side effects of the vaccine. These findings are similar to previous research which reveal several reasons individuals choose to refuse vaccines [53]. The results from the first theme (reasons to refuse COVID-19 vaccines) show that users raise important and legitimate concerns…”
Section: Discussionsupporting
confidence: 90%
“…A positive association was observed between male gender and intention of HCPs to accept COVID-19 vaccination, as in other previous studies [18,23,24,38]. The decisionmaking process of vaccination acceptance may be influenced by the perceptions of risk from COVID-19.…”
Section: Discussionsupporting
confidence: 79%
“…Females were more unsure. Lack of data for vaccine safety has been reported as the main reason for unwillingness [18]. A national survey in the United States revealed that 42.4% of participants were hesitant to be vaccinated against COVID-19, and approximately 1 in 10 did not intend to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…French hesitancy against the COVID-19 vaccine was already measurable in the general population at the height of the first wave in March 2020 [ 37 ]. COVID-19 vaccination was lower than in other European countries [ 38 , 39 ]. The COVID-19 vaccine refusal was 29.4% (95% CI 28.6–30.2) of the French working-age population and was significantly associated with female gender, age, lower educational level, poor compliance with recommended vaccinations in the past, no chronic conditions and lower perceived severity of COVID-19 [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%